'The Drugs Did For Me What I Couldn't Do For Myself': A Qualitative Exploration of the Relationship Between Mental Health and Amphetamine-Type Stimulant (ATS) Use. (December 2021) - Spencer, Liam Patrick; Addison, Michelle; Alderson, Hayley; McGovern, William; McGovern, Ruth; Kaner, Eileen; O'Donnell, Amy
Substance use and mental ill health constitute a major public health burden, and a key global policy priority is to reduce illicit and other harmful substance use. Amphetamine-type stimulants (ATS) are the second most used class of illicit drugs and a range of mental health issues have been documented amongst users. This paper explores the relationship between mental health and ATS use, through a thematic analysis of qualitative interviews with n  =  18 current and former ATS users in England. The findings are presented by trajectory point of; (1) Initiation of ATS use; (2) continued and increased ATS use and (3) decreased and remitted ATS use. This work helps to develop understanding around the complex and bi-directional relationship between ATS use and mental health. Many ATS users lead chaotic lives and engage in multiple risk behaviours, however there is a need to better understand and conceptualise the dynamic interaction between different individual, social, environment and cultural factors that determine individuals' mental health and substance use. There is no 'one size fits all' approach to prevention and treatment, and these findings highlight the need for more joined-up, tailored and holistic approaches to intervention development.